Endocardial contact mapping of the left atrial appendage in persistent atrial fibrillation - Takahashi, Yoshihide; Akiyoshi, Kikou; Sekigawa, Masahiko; Yagishita, Atsuhiko; Yamamoto, Tasuku; Maeda, Shingo; Kawabata, Mihoko; Goya, Masahiko; Hirao, Kenzo; Sasano, Tetsuo (Journal of cardiovascular electrophysiology, 2020)
Introduction Isolation of the left atrial appendage (LAA) is often performed in persistent atrial fibrillation (AF). Propagation patterns in the LAA during AF remain to be elucidated. We sought to characterize propagation patterns in the LAA during AF in persistent AF. Methods Persistent AF patients undergoing catheter ablation were studied. Pulmonary vein isolation (PVI) was performed during continuous AF. If AF was not terminated by PVI, bi‐atrial mapping was performed using a multi‐electrode catheter during AF. Maps were collected at each site for 30 seconds and analyzed offline with a novel software, CARTOFINDER. This software made automatic determinations of whether activation was focal or rotational. The left atrium (LA) was divided into five regions, of which the LAA was one, and the right atrium (RA) into three. Results Eighty patients were studied (62 ± 10 years, 65 males). On average, 9.6 ± 2.2 and 4.1 ± 1.2 maps were created in the LA and RA, respectively. The LAA was mapped in 70 patients, resulting in 85 maps. In the LAA, activation was identified as focal more often than rotational (64 [91%] vs 10 [14%] patients, P < .001), seven patients displayed both. The number of focal activation events was greatest in the LAA (28.5 events/30 seconds [interquartile range, 15‐54]) of the eight atrial regions. During focal activation, sites designated as earliest activation frequently covered a wide area, rather than being localized to a discrete site (5.4 ± 3.1 electrodes). Conclusions The results of this study suggest that focal activation is a major mechanism underlying the arrhythmogenicity of the LAA in persistent AF.